Efek Dan Konstribusi Penggunaan Strategi Konflik Kognitif Berbasis Model Inkuiri Terhadap Peningkatan Kemampuan Berpikir Kritis Mahasiswa - Ni Nyoman Sri Putu Verawati; Wahyudi Wahyudi; Muhammad Taufik (Department of Physics Education, Universitas Mataram, 2018)
This study aims to determine the effect of the use of cognitive conflict strategies in inquiry-based learning models and its contribution to improving critical thinking ability of physics prospective teacher. This research is an experimental study with a pretest-posttest control group design. The research samples was taken with a purposive sampling technique with criteria for physics prospective teacher were taking the fundamental physics course as many as 2 (two) classes that would be used as the experimental and control group. The research data were analyzed descriptively and statistically (inferential) using the Statistical Package for Social Science (SPSS) 23.0. The results showed that the use of cognitive conflict strategies in inquiry-based learning models had a positive impact and contributed to the improvement of critical thinking ability of physics prospective teacher. Further description of the research conducted is presented in this article.